2022
DOI: 10.3389/fmed.2022.802412
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Platelet Count and In-hospital Mortality in Adult Patients With COVID-19: A Retrospective Cohort Study

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) has become a global pandemic. Systemic inflammation in COVID-19 patients has been associated with poor clinical outcome. This study aims to determine the relationship between platelet count and in-hospital mortality.MethodsThe original data of this study were from article development and validation of a predictive model of in-hospital mortality in COVID-19 patients. In this secondary analysis, we adopted multi-variable logistic regression analyses and smooth cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In this study, leukocytosis, neutrophilia, lymphopenia and thrombocytopenia were more frequently seen in non-survivor patients with diabetes. Several studies (Abd El-Lateef et al, 2022;Loomba et al, 2022;Malik et al, 2021;Niu et al, 2022;Yang, Gao, et al, 2022; found lymphopenia and thrombocytopenia as independent predictors of poor outcome which is also consistent with our study. Won et al, 2022).…”
Section: Interpretation In the Context Of The Wider Literaturesupporting
confidence: 93%
“…In this study, leukocytosis, neutrophilia, lymphopenia and thrombocytopenia were more frequently seen in non-survivor patients with diabetes. Several studies (Abd El-Lateef et al, 2022;Loomba et al, 2022;Malik et al, 2021;Niu et al, 2022;Yang, Gao, et al, 2022; found lymphopenia and thrombocytopenia as independent predictors of poor outcome which is also consistent with our study. Won et al, 2022).…”
Section: Interpretation In the Context Of The Wider Literaturesupporting
confidence: 93%
“…The new models contain 7 confounding variables, including age, GCS score, endovascular therapy, Charlson comorbidity index, sepsis, Clipping, and sex. It was explored whether there was a curve relationship between T-lowest and in-hospital mortality using restricted cubic spline analysis 26 . We conducted interaction and stratified analyses based on GCS (< 8 and ≥ 8 scores), sex, and age (< 60 and ≥ 60 years).…”
Section: Methodsmentioning
confidence: 99%
“…The threshold effect of bicarbonate is determined using a two-piecewise linear regression model if a non-linear connection is observed. The linear model was contrasted using the log-likelihood ratio test as well ( 19 ). Interaction and stratified analyses were performed for age (<60 years and ≥ 60 years), sex, myocardial infarction, congestive heart failure, hypertension, diabetes, sepsis, endovascular aneurysm treatment, and GCS (<8 and ≥ 8 scores).…”
Section: Methodsmentioning
confidence: 99%